“Diagnostic pathways in femoroacetabular impingement, patterns of clinical visits, and MRI utilization before hip arthroscopy in Türkiye” - Saygin Kamaci; Barlas Goker; Izzet Bingol; Ulas Can Kolac; Niyazi Erdem Yasar; Ali Aykut Fidanci; Naim Ata; M. Mahir Ulgu; Suayip Birinci; Asim Kayaalp; Tahsin Beyzadeoglu; Bulent Atilla; et al. (Scientific Reports)
Abstract Diagnosing femoroacetabular impingement (FAI) is challenging and surgical indications for hip arthroscopy are still evolving. This study analyzes the two years leading up to surgery in a large cohort of patients with FAI. We hypothesized that patients with FAI experience diagnostic challenges causing delayed treatment. We assessed the 2-year diagnostic journeys of patients prior to hip arthroscopy by analyzing recurring hip-related hospital visits, magnetic resonance imaging (MRI), the geographical distribution, and healthcare settings of these visits related to hip pain using data from a nationwide database. Medical records in the national e-health database were reviewed to identify patients who underwent hip arthroscopy between January 2017 and May 2023. Patients aged 18–65 years with a minimum of 2 years of prior medical records were included. The number of clinic visits and MRI scans in the 2 years prior to hip arthroscopic FAI surgery were analyzed with distributions of age and sex. 1754 patients who were confirmed to have complete procedure notes were included in the study. Only 30 of the 81 provinces of Türkiye had hip arthroscopy entries (37.0%). The majority of patients presented at university hospitals on their first visit (35.3%), and 1544 patients (88%) underwent MRI prior to surgery. The median number of clinic visits was 9 (SD: 7.7) and that of MRI scans was 2 (range: 1–7) per patient. Patients under 40 years had a higher mean of orthopedic surgery clinic visits (M: 8.8, SD: 5.1) than those over 40 years (M: 8.1, SD: 6.0) (p = 0.01). There was no significant difference between men and women in mean orthopedic clinic visits (8.5 vs. 8.4, respectively). The findings suggest that patients with FAI undergo a considerable number of physician visits (median of 9) and MRI scans (median of 2) in the 2 years preceding hip arthroscopy in Türkiye. These results may indicate diagnostic challenges, delays in determining the need for surgery, and potential reluctance to undergo hip arthroscopy. Addressing these issues would require implementing strategies to reduce the time from symptom onset to treatment initiation and alleviate the financial burden associated with delayed diagnosis.